Use of Forest Products Who Lives in Mountain Areas of Mersin Province - Sedef Akıncı; Dilek Bostan Budak (Turkish Journal of Agriculture: Food Science and Technology)
In the study, which is conducted in mountain villages of Mersin province, 99 people selected by simple random sampling method. The data were collected by face to face interviewed. 64.6% of the individuals were male, 35.4% female and 35.4% had a primary school diploma. The average household width was 2.38 and the average age was 50.32. Small ruminant and beekeeping activities are the main source of livelihood for individuals who lives in mountain villages, but also they are benefiting from forest products. As forest products, medicinal aromatic plants such as centaury, thyme, rosehip, mushrooms, blackberries, carob, and straw are used. Men work more intensively in jobs such as wood, timber and resin, which require heavy labour, while products such as centaurs, blackberries and rosehips are collected by women. Individuals' perceptions of forest and forest products do not change according to gender, age and education level. This is because they need the forest and its’ products to maintain their lives. In general, it is determined that the population living in the mountain villages live a life based on forest and forest products. In this context, protection of forest areas in the region is very important both for the prevention of environmental damage and for the people of the region. In addition to individual awareness, support should be provided by the relevant ministries on the use and protection of forests and products. The aim of this study was to identify the use of forest products and opinion about forest who lives in mountain villages of Mersin.